Fibro-osseous lesions of craniofacial bones in children: case reports - Vankevičiūtė, Rasa Aurelija; Neverauskienė, Arijanda; Lukoševičius, Evaldas (Acta medica Lituanica, 2013)
Background. The aim of this article is to present rare clinical cases of craniofacial fibro-osseous lesions in pediatric patients. Materials and methods. In this report we present 3 cases of fibroosseous craniofacial lesions in pediatric patients. Lesions of bones resembled fibrous dysplasia, dysplastic fibroma and chronic osteomyelitis which were confirmed or suspected by clinical signs, radiographic visualization methods and histopathological investigations for these patients. The diagnostic workup, treatment, follow-up procedures and a literature review are presented. Results and conclusions. Fibro-osseous lesions of the jaws and skull manifest in a similar pattern. Conditions are easily revealed upon examination and with the help of conventional diagnostics, however, differential diagnosis using only radiological imaging is impossible. Histological findings remain a tool of choice determining the treatment strategy and outcome of the patients but it is not always available due to anatomical and functional considerations. Treatment of fibro-osseous lesions of the face and skull is highly individualized and depends on various qualities of the lesion and the patient himself. All patients received palliative symptomatic treatment to alleviate their conditions and in all cases obtaining a histology specimen and surgical intervention for treatment of the lesion was considered as a treatment option only if it was seen being safe and as least traumatic as possible because of the functional and psychological importance of the craniofacial region.